Edukasi Program Skrining Hipotiroid Kongenital Pada Kelompok Masyarakat Di Kelurahan Lambung Bukit Kota Padang - Wardiah, Rizalia; Roza, Shelvy Haria; Yosalli, Yosalli (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Congenital Hypothyroidism is a health disorder caused by a deficiency of thyroid hormones starting from the womb, which can lead to growth issues, mental retardation, and disabilities. The prevention of such complications is carried out through Congenital Hypothyroidism Screening (SHK). The SHK program is a preventive initiative aimed at preventing developmental disorders in children. Although it has not yet reached its full potential, the SHK program has been implemented in various regions across Indonesia. Padang City, West Sumatra, has implemented the SHK program in several hospitals as a strategic effort for the early detection of thyroid disorders. Based on the results of thyroid function screening at RSI Siti Rahmah Padang in 2023, it was found that 99.3% of 150 newborns had euthyroid TSH levels, while 0.7% experienced hypothyroidism. The objective of this community service project is to increase public knowledge regarding the Congenital Hypothyroidism Screening (SHK) program. The method used in this activity involved educational sessions followed by a pre-test and post-test. The pre-test results showed a mean score of 4.13, with a range of 2 to 7. Meanwhile, the mean score increased in the post-test to 8.37, with a range of 6 to 9. This indicates a significant increase in public knowledge regarding the SHK program among the community in Lambung Bukit Village, Pauh District, Padang City.